Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the system of equations:
[tex]\[ \begin{array}{c} y = 2x^2 - 9x + 7 \\ y = 2x - 2 \end{array} \][/tex]
we can set the two equations equal to each other since they both equal [tex]\( y \)[/tex]. This gives:
[tex]\[ 2x^2 - 9x + 7 = 2x - 2 \][/tex]
Next, we will move all terms to one side of the equation to set it to 0:
[tex]\[ 2x^2 - 9x + 7 - 2x + 2 = 0 \][/tex]
Combine like terms:
[tex]\[ 2x^2 - 11x + 9 = 0 \][/tex]
Now, we solve the quadratic equation [tex]\( 2x^2 - 11x + 9 = 0 \)[/tex] using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our equation [tex]\( 2x^2 - 11x + 9 = 0 \)[/tex], [tex]\(a = 2\)[/tex], [tex]\(b = -11\)[/tex], and [tex]\(c = 9\)[/tex]. Substituting these values into the quadratic formula, we get:
[tex]\[ x = \frac{-(-11) \pm \sqrt{(-11)^2 - 4 \cdot 2 \cdot 9}}{2 \cdot 2} \][/tex]
Simplify inside the square root:
[tex]\[ x = \frac{11 \pm \sqrt{121 - 72}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm \sqrt{49}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm 7}{4} \][/tex]
This results in two potential solutions for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{11 + 7}{4} = \frac{18}{4} = \frac{9}{2} \][/tex]
[tex]\[ x = \frac{11 - 7}{4} = \frac{4}{4} = 1 \][/tex]
Now, let's check which of these possible values of [tex]\( x \)[/tex] match the given options:
A) [tex]\(-1\)[/tex] \\
B) [tex]\(\frac{7}{2}\)[/tex] \\
C) [tex]\(\frac{9}{2}\)[/tex] \\
D) [tex]\(\frac{11}{2}\)[/tex]
The value [tex]\( x = 1 \)[/tex] is not listed in the given options. However, [tex]\( x = \frac{9}{2} \)[/tex] is indeed one of the provided options.
Therefore, the correct answer is:
[tex]\[ \boxed{\frac{9}{2}} \][/tex]
[tex]\[ \begin{array}{c} y = 2x^2 - 9x + 7 \\ y = 2x - 2 \end{array} \][/tex]
we can set the two equations equal to each other since they both equal [tex]\( y \)[/tex]. This gives:
[tex]\[ 2x^2 - 9x + 7 = 2x - 2 \][/tex]
Next, we will move all terms to one side of the equation to set it to 0:
[tex]\[ 2x^2 - 9x + 7 - 2x + 2 = 0 \][/tex]
Combine like terms:
[tex]\[ 2x^2 - 11x + 9 = 0 \][/tex]
Now, we solve the quadratic equation [tex]\( 2x^2 - 11x + 9 = 0 \)[/tex] using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For our equation [tex]\( 2x^2 - 11x + 9 = 0 \)[/tex], [tex]\(a = 2\)[/tex], [tex]\(b = -11\)[/tex], and [tex]\(c = 9\)[/tex]. Substituting these values into the quadratic formula, we get:
[tex]\[ x = \frac{-(-11) \pm \sqrt{(-11)^2 - 4 \cdot 2 \cdot 9}}{2 \cdot 2} \][/tex]
Simplify inside the square root:
[tex]\[ x = \frac{11 \pm \sqrt{121 - 72}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm \sqrt{49}}{4} \][/tex]
[tex]\[ x = \frac{11 \pm 7}{4} \][/tex]
This results in two potential solutions for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{11 + 7}{4} = \frac{18}{4} = \frac{9}{2} \][/tex]
[tex]\[ x = \frac{11 - 7}{4} = \frac{4}{4} = 1 \][/tex]
Now, let's check which of these possible values of [tex]\( x \)[/tex] match the given options:
A) [tex]\(-1\)[/tex] \\
B) [tex]\(\frac{7}{2}\)[/tex] \\
C) [tex]\(\frac{9}{2}\)[/tex] \\
D) [tex]\(\frac{11}{2}\)[/tex]
The value [tex]\( x = 1 \)[/tex] is not listed in the given options. However, [tex]\( x = \frac{9}{2} \)[/tex] is indeed one of the provided options.
Therefore, the correct answer is:
[tex]\[ \boxed{\frac{9}{2}} \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.